2017
DOI: 10.4269/ajtmh.16-0756
|View full text |Cite
|
Sign up to set email alerts
|

Nonacademic Attributes Predict Medical and Nursing Student Intentions to Emigrate or to Work Rurally: An Eight-Country Survey in Asia and Africa

Abstract: We sought to identify independent, nonacademic predictors of medical and nursing student intent to migrate abroad or from rural to urban areas after graduation in low- and middle-income countries (LMIC). This was a cross-sectional survey of 3,199 first- and final-year medical and nursing students at 16 training institutions in eight LMIC. Questionnaires assessed demographics, career intentions, and preferences regarding selected career, location, and work-related attributes. Using principal component analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Similar results were reported in a survey of eight low-and middleincome countries in Asia and Africa. In addition, it was found that work environment resources, location livability and employment conditions were non-medical factors that could affect intention to work in rural areas or to leave (24). Physicians, like other professionals, look for better living standards and professional development, This issue plays a significant role in their retention rate in rural areas (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported in a survey of eight low-and middleincome countries in Asia and Africa. In addition, it was found that work environment resources, location livability and employment conditions were non-medical factors that could affect intention to work in rural areas or to leave (24). Physicians, like other professionals, look for better living standards and professional development, This issue plays a significant role in their retention rate in rural areas (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-two percent of the articles-from 12 Asia-Pacific LMICs-were about educational factors, categorized into 2 areas: (1) student selection, and; (2) delivering medical education. For student selection, most studies demonstrated rural background was associated with both rural preference [33][34][35][36][37][38][39][40][41][42][43][44][45][46]54] and actual work [26], while several found no association with rural preference [47][48][49]56]. Being enrolled through the 'special track' , which consists of rural student recruitment, scholarships and receive a rural-oriented curriculum, were associated with actual work in rural areas [27][28][29][30][31][32].…”
Section: Educationalmentioning
confidence: 99%
“…There are mixed findings about association between rural recruitment and rural work preference. While the majority of studies agree that having rural background is associated with rural work preference [33][34][35][36][37][38][39][40][41][42][43][44][45][46], three studies found no difference [47][48][49] b) Students who are native to specific locations ‡…”
Section: Preference Bmentioning
confidence: 99%
“…A second is whether one has actually grown up (or trained) in an area of need, such as an LMIC rural area, in which case emigration is less likely. 13 Understanding what motivates or enables some professionals to leave and others to stay under similar circumstances is a perennial question in skilled/professional migration research that cannot be fully examined through quantitative methods alone. We have explored the determinants of medical migration and health personnel retention in Sub-Saharan African countries using both quantitative data from the American Medical Association Masterfile and qualitative data from in-depth interviews with both African-based medical practitioners and US-based African medical graduates.…”
mentioning
confidence: 99%
“…Research suggests certain non-academic attributes such as individualism and altruism can predict medical and nursing students' intention to emigrate or to stay and serve rural and remote areas in LMICs. 13 While the quality and extent of such evidence should be systematically evaluated before making any lasting policy, as community psychologist, public health professor, and pediatrician respectively, we believe it important to consider such dispositional attributes in the recruitment of trainees in caring professions like medicine and nursing. Further, social and behavioral theories and research on place attachment, place identity, and sense of community provide insight into the psychosocial processes that bond individuals with their native communities and places.…”
mentioning
confidence: 99%